Two-fractionated stereotactic magnetic resonance-guided adaptive radiation therapy for patients with prostate cancer (SMART PRO trial): protocol for a confirmatory clinical trial - Sadamoto Zenda; Takashi Kawaguchi; Takashi Uno; Tairo Kashihara; Tetsuo Saito; Hiroyuki Okamoto; Noriyuki Kadoya; Takahiro Chiba; Shin-ei Noda; Keiichi Jingu; Keiko Shibuya; Hiroshi Igaki (BMJ Open, 2024)
Introduction In an MRI-guided linear accelerator (MR-LINAC) system, the planned doses for organs at risk and for tumours are assessed by MR imaging and re-contouring at every treatment. This allows treatment to be safer and more precise by ensuring that it is suitable for the state of the patient’s organs on that day, as well as by allowing images to be acquired during radiation therapy to prevent radiation while organs are in motion.Here, we will conduct a confirmatory study of two-fractionated stereotactic magnetic resonance-guided adaptive radiation therapy for patients with localised prostate cancer.Methods and analysis This will be a single-arm study to demonstrate the safety and efficacy of ultra-hypofractionated radiation (26 Gy/2 Fr) using an MR-LINAC system in patients with very low-intermediate risk prostate cancer.The primary endpoint will be the incidence of grade ≥2 acute urinary tract adverse events occurring within 90 days of the start of radiation therapy.The sample size has been determined to be 58.Ethics and dissemination This study is performed in accordance with Ethical Guidelines for Medical and Health Research Involving Human Subjects, published by Japan’s Ministry of Education, Science and Technology and the Ministry of Health, Labour and Welfare and the modified act on the Protection of Personal Information as well as the Declaration of Helsinki. This study was approved by the institutional ethics committee of the National Cancer Center on 20 November 2021.The findings of this trial will be submitted to an international peer-reviewed journal and the key findings will be presented at an international scientific conference.Authorship will be ascribed in accordance with the International Committee of Medical Journal Editors guidance.Trial registration number UMIN000049746.